2019
DOI: 10.1111/are.14095
|View full text |Cite
|
Sign up to set email alerts
|

Defining Dermo resistance phenotypes in an eastern oyster breeding population

Abstract: Perkinsus marinus, the causative agent of Dermo disease, is responsible for mass mortalities and negatively impacts aquaculture production of the eastern oyster, Crassostrea virginica. Selective breeding is a viable option for Dermo disease management; however, fluctuations in natural selection pressure and environmental noise hinder accumulation of genetic gains acquired through field performance trials. The purpose of this study was to adapt and apply laboratory disease challenge methods to eastern oysters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To estimate infection levels in each sampled oyster, 1 µL diluted DNA was added to a P. marinus -specific quantitative polymerase chain reaction (qPCR) assay ( De Faveri et al, 2009 ). Parasite load was initially measured as the number of P. marinus DNA copies in 100 ng of total DNA and subsequently converted to (log) spores g −1 wet tissue weight as described in Proestou et al (2019) . Mantle tissue is recommended when using PCR-based methods to diagnose and quantify the intensity of dermo disease by the World Organization of Animal Health (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate infection levels in each sampled oyster, 1 µL diluted DNA was added to a P. marinus -specific quantitative polymerase chain reaction (qPCR) assay ( De Faveri et al, 2009 ). Parasite load was initially measured as the number of P. marinus DNA copies in 100 ng of total DNA and subsequently converted to (log) spores g −1 wet tissue weight as described in Proestou et al (2019) . Mantle tissue is recommended when using PCR-based methods to diagnose and quantify the intensity of dermo disease by the World Organization of Animal Health (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…We restricted our RNAseq and expression analyses to individuals censored at Day 7 post-injection. These oysters were the focus because previous work identified peak infection intensities and significant transcriptomic responses to the parasite at this time point ( Proestou et al, 2019 ; Proestou and Sullivan, 2020 ). Specific animals were selected based on the median (log) spores g −1 wet weight for each group to minimize within group variation in transcriptomic response to the parasite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting lines have been experimentally tested across the range of eastern oyster production, and survivorship was generally superior compared to wild oysters, although oysters had greater survival in areas where they were selectively bred making the comparison more difficult [61,62]. Laboratory challenge of oysters with P. marinus revealed that there was a 54.1% difference in survival between two families in 2014, but no significant family effect was observed when the challenge was repeated in 2015 [63]. This demonstrates that while breeding programmes based on mass selection can achieve significant results, it is more difficult to develop an understanding of disease resistance as environmental factors are highly variable.…”
Section: Practical Applications Of Breeding For Disease Resistancementioning
confidence: 99%